Online Learning in Higher Education: Analysis during the Pandemic Covid-19 - Rifqi Zaeni Achmad Syam; Willya Achmad (Jurnal Mantik, 2022)
This research aims to determine the effectiveness and teaching quality of UNINUS Bandung teachers' and the quality of learning. Online learning is the most important tool in the learning process during the Covid 19 pandemic. The research method is to use Likert questionnaire survey. The subjects of the studied were students of the Nusantara Islamic University in Bandung who receive online training. The results of this study show that the effectiveness of online learning during the Covid 19 pandemicis in the low category. The implementation of online learning during the Covid 19 pandemic is as follows: students have difficulty in understanding materials, online lectures are boring, online learning support equipment is insufficient, connection is not good, and the motivation of students to participate in learning has decreased. and then follow up on the students who have also declined than before. Achievement. Online learning outlines a suboptimal understanding of the material, which makes the reading process ineffective. It can be used to gain understanding when learning online, and teachers should use zoom or googlemeet media.